Study on anti-collapse performance of CFST structures under collision load in different cases. - Lian Song; Lin Wang; Xuan Wang (PLoS ONE)
In view of the continuous collapse resistance of the remaining structure under impact column and side columns under vehicle loads, the composite plane frame of concrete filled steel tubes (CFST) was established by using the finite element software ABAQUS, and the orthogonal experimental design and analysis were carried out. Through numerical analysis, the whole process of continuous collapse of the structure caused by low-speed impact is simulated. The research results show that: in the collapse mechanism of the two working conditions, the deformation modes of the impact column and the remaining frame show two modes. According to the fact that the axial force of the adjacent bottom column of the non-impact column increases greatly at first and then tends to be stable after being impacted, the axial force of the non-adjacent bottom column fluctuates up and down around the impact front axle force. Comparing the two working conditions with the direct simulation method (DS) and the alternate path method (AP), the reliability of AP method in evaluating the internal force of the remaining structure under impact load is insufficient, and it is unsafe to judge the collapse degree of the structure. According to the result of range analysis, it can be seen that the velocity is the most important factor to cause the dynamic effect of the remaining structure in the two cases. This study deeply analyzes the influence of the structural damage caused by the low-speed impact of accidents on the continuous collapse of the remaining structures, which has very important theoretical and practical significance for improving the anti-continuous collapse ability of buildings.